Analisis Sistem Pembelajaran Daring (SPADA) dalam Mata Kuliah Menulis Teks Berbahasa Jawa - Veronika, Prima (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This study aims to analyze the Online Learning System (SPADA) in the Javanese Text Writing course. This type of research is a qualitative descriptive study using interpretive methods presented in the form of a description. The research subjects were students of the Java Language Education Study Program (PBJ) FKIP UNS semester II or the 2020 batch of 74 people. The sample was taken using a purposive sampling technique which only focused on students who were taking the MTBJ course in the even semester of 2021. The data collection technique used a questionnaire or questionnaire technique. The analysis technique used is data collection, data processing and giving conclusions. Data processing is presented in the form of a brief description or detailed narrative text. The data that has been obtained are categorized and then conclusions are drawn. The results showed that students got various conveniences and benefits, such as ease of remembering lecture history, improvement of IT skills, ease of sending assignments, ease of understanding theory and improving skills as well as increasing the effectiveness of the lecture process. The SPADA features or menus that are much favored by students while attending MTBJ lectures, which can increase the effectiveness of lectures are discussion forums, assignments, course materials, and my dashboard. Some improvements that must be made by SPADA are related to upgrading the system, added features, and lecturer skills improvement.